2019
DOI: 10.1016/j.cegh.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of postpartum depression and cesarean section: A systematic review and meta-analysis

Abstract: Postpartum depression (PPD) is a major depressive disorder. Its symptoms begin 4 weeks after delivery. Several studies have evaluated the association of the type of delivery with PPD; however, there are controversies regarding this association. Therefore, the aim of this systematic review was to estimate the overall association between cesarean section (CS) and PPD. Methods: The international databases of Medline, Scopus, Web of Science, Science Direct, EMBASE and Ovid were searched until May 2017. Quality ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
5
23
0
9
Order By: Relevance
“…19 36 39 40 Two meta-analyses clearly showed increased risk due to caesarean section. 41 42 However, most of the studies were small and from a single institution. Only two studies reported a higher risk with vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…19 36 39 40 Two meta-analyses clearly showed increased risk due to caesarean section. 41 42 However, most of the studies were small and from a single institution. Only two studies reported a higher risk with vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, os resultados se tornaram não significativos após o controle dos níveis de sofrimento pré-natal. Por fim, as mulheres que realizaram parto cesáreo apresentaram níveis mais elevados de estresse, ansiedade e depressão pré-natal em relação às mulheres que não realizaram o procedimento (MOAMERI H, et al, 2019).…”
Section: Fatores De Risco Para Depressão Pós-partounclassified
“…É inegável a importância obstétrica da cesárea, procedimento que já salvou milhares de mães e recémnascidos. Nesta perspectiva, com os avanços tecnológicos e sociais, a cesárea passou de uma operação obstétrica específica para emergências para um modo relativamente comum de concepção humana (CHEN HH, et al, 2017;MOAMERI H, et al, 2019). As taxas de realização desse procedimento em todo o mundo são crescentes, excedendo em muitos locais 20% do total de partos, taxa significativamente maior do que a taxa de 15% considerada a mais alta aceitável pela Organização Mundial da Saúde (OMS) (CHANG SR, et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…One large birth cohort found no association between mode of delivery and postnatal emotional distress 1 and findings from the United Kingdom's Avon Longitudinal Study of Parents and Children suggested elective caesarean section (ELCS) was not protective for postnatal depression 2 and that women who undergo emergency caesarean section (EMCS) may be reassured regarding their additional risk of postnatal depression. However, one meta‐analysis showed caesarean section to be a weak risk factor for postnatal depression 3 . Similarly, the consequences of emergency caesarean may increase the risk of postnatal depression 4 …”
Section: Introductionmentioning
confidence: 99%